CONCRETE DYNAMISM IN WOMEN’S LITERATURE IN THE 19TH CENTURY - Sasidhar, A. Pavani; Kumar, P.V. Ravi (International Journal of Psychosocial Rehabilitation, 2020)
The paper discusses the impact of female authors in the nineteenth-century who used literature as a medium to incite changes in the unjust position of women in the society. External factors such as author gender, author nationality, and date of publication affect both the choice of literary themes in novels and the expression of those themes, but the extent of this association is difficult to quantify. The full and equal political participation of women is a prerequisite for democratic governance. However, globally, girls and women continue to be marginalized from the political sphere due to restrictive laws and institutional barriers, discriminatory cultural practices, and disproportionately low access to quality education, healthcare, and resources. Yet reversing discriminatory policies and practices is possible and has been done. Over the last two decades, but particularly in the last ten years, research into sex, gender and politics has become an established sub-field of political science. This article opens with some reflections on the position of ‘women and politics’ scholars and research within the British political science community. It then moves on to reflect upon the burgeoning literature on women’s political representation. In particular, it questions the way in which the relationship between women’s descriptive and substantive representation has been operationalised and investigated in empirical research, namely through the concept of critical mass. Seeking to reframe these debates, the article suggests that future research should focus not on the question of when women make a difference, but on how the substantive representation of women occurs.